Costimulatory effect of rough calcium phosphate coating and blood mononuclear cells on adipose-derived mesenchymal stem cells in vitro as a model of in vivo tissue repair; Materials; Vol. 13, iss. 19 - Khlusov I. A. Igor Albertovich; Litvinova L. S. Larisa Sergeevna; Shupletsova V. V. Valeria Vladimirovna; Khaziakhmatova O. G. Olga Gennadjevna; Malashchenko V. V. Vladimir Vladimirovich; Yurova K. A. Kristina Alekseevna; Shunkin E. O. Egor Olegovich; Krivosheev V. V.; Porokhova E. D. Ekaterina Danilovna; Sizikova A. E. Anastasiya Evegnjevna; Safiullina L. A. Linara Askhatovna; Legostaeva E. V. Elena Viktorovna; et al. (2020, 2020)
Title screen